Possible role of SCN4A skeletal muscle mutation in apnea during seizure - TÜRKDOĞAN, DİLŞAD; ULUÇ, KAYIHAN (WILEY, 2019)
SCN4A gene mutations cause a number of neuromuscular phenotypes including myotonia. A subset of infants with myotonia-causing mutations experience severe life-threatening episodic laryngospasm with apnea. We have recently identified similar SCN4A mutations in association with sudden infant death syndrome. Laryngospasm has also been proposed as a contributory mechanism to some cases of sudden unexpected death in epilepsy (SUDEP). We report an infant with EEG-confirmed seizures and recurrent apneas. Whole-exome sequencing identified a known pathogenic mutation in the SCN4A gene that has been reported in several unrelated families with myotonic disorder. We propose that the SCN4A mutation contributed to the apneas in our case, irrespective of the underlying cause of the epilepsy. We suggest this supports the notion that laryngospasm may contribute to some cases of SUDEP, and implicates a possible shared mechanism between a proportion of sudden infant deaths and sudden unexpected deaths in epilepsy.
Keywords: laryngospasm; SUDEP; myotonia; sodium channel